2015
DOI: 10.1161/jaha.115.002010
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mimecan Is Associated With Arterial Stiffness in Hypertensive Patients

Abstract: BackgroundMimecan plays an important role in endothelial and vascular smooth muscle cell integrity and may be involved the pathology of arterial stiffness. However, the role of mimecan in arterial stiffness in patients with hypertension is not well defined.Methods and ResultsA total of 116 hypertension patients and 54 healthy controls were enrolled in the investigation. Hypertensive patients were divided into 2 groups: the with arterial stiffness group (brachial-ankle pulse wave velocity [baPWV] ≥1400 cm/s; n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Based on a cross-section study of 14866 hypertensive participants, this study found that baPWV ≥1400 cm/s was universal in hypertensive participants, with a prevalence of 87.2%. It was nearly the same as research by Zhang et al [23] and Gu et al [24], although the studies were based on different size of sample. In addition, almost half of the hypertensive participants in our study were considered in one study to be at risk of moderate arteriosclerosis, which has been considered to be an independent factor in indicating the relapse of cardiovascular diseases (CVD) as well as an irreversible progress of AS [25].…”
Section: Discussionsupporting
confidence: 55%
“…Based on a cross-section study of 14866 hypertensive participants, this study found that baPWV ≥1400 cm/s was universal in hypertensive participants, with a prevalence of 87.2%. It was nearly the same as research by Zhang et al [23] and Gu et al [24], although the studies were based on different size of sample. In addition, almost half of the hypertensive participants in our study were considered in one study to be at risk of moderate arteriosclerosis, which has been considered to be an independent factor in indicating the relapse of cardiovascular diseases (CVD) as well as an irreversible progress of AS [25].…”
Section: Discussionsupporting
confidence: 55%
“…It is excreted to urine after glomerular filtration. Gu et al 29 found that the level of baPWV was increased with the elevation of creatinine, and creatinine was an independent risk factor of arterial stiffness in hypertensive. Resting heart rate has recently been regarded as cardiovascular risk factor in the general population as well as in individual persons suffered from cardiovascular diseases 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive patients have a higher ET-1 than healthy controls. 18 Circulating levels of ET-1 and endogenous ET(A)-mediated constriction are increased in human aging. 19 ET-1 is also involved in progression of renal hypertension.…”
Section: Discussionmentioning
confidence: 99%